Optimisation of alkaline extraction of protein from brewer's spent grain. Issue 4 (7th September 2022) - Karlsen, Freja; Lund, Ivar; Skov, Peter V.
Abstract : Extraction of proteins from industrial residues is a potential source for animal feed. Alkaline extraction combined with isoelectric precipitation may be a useful method for isolating protein from brewer's spent grain (BSG), an abundant by‐product from the brewing industry. The objective of this study was to examine the effect of temperature (30, 45 and 60°C), time (30, 60, 120 and 180 minutes), agitation (shaking and stirring), precipitation salinity (0.5 M sodium chloride), isolation mode (freeze drying and precipitation), pre‐treatment (defatting and delignification) and repeated extraction on the protein yield and protein content from BSG. Generally, the protein content decreased while protein yield increased with increasing extraction temperatures. Yield and content were maximised after 30 minutes reaching the highest protein content at 30 o C (54.8%) and the highest protein yield at 60 o C (10.5%). Precipitation with 0.5 M sodium chloride reduced the protein content to 36.4% and the yield to 4.2%. Freeze drying combined with triple extraction yielded a protein content of 20‐25%, together with a relatively high protein yield (ca. 45‐50%). Delignification increased the protein content from 27% to 32% whereas defatting reduced the overall protein yield from 45% to 38%. Combining isoelectric precipitation and single extraction was associated with a higher protein content (40‐55%) but poor protein yields (5‐10%). In the light of these findings, further research is required to establish conditions that maximise both the protein content and yield. © 2022 The Institute of Brewing & Distilling.